Openness and Sensing Capacity: The Case of Micro and Small Furniture Industries in Tanzania - Yohana Jacob Sesabo; Mushumbusi Paul Kato; Emmanuel James Chao (CV. Literasi Indonesia, 2023)
Mainstream open innovation (openness) research has directly linked it to innovation performance, leaving intermediary processes such as innovation opportunity recognition (sensing capacity) not fully explained. This study examined the relationship between openness (inbound and coupled openness) and sensing capacity. The study surveyed a quota sample of 213 micro and small furniture industries (MSFIs) in Tanzania’s cities of Arusha, Mbeya, and Dar es-salaam and applied a close-ended questionnaire to collect data from owners (managers) of the micro and small furniture industries. Subsequently, the study used partial least square structural modeling (PLS-SEM) to analyze the data and found that inbound openness positively affects sensing capacity directly and indirectly through coupled openness. Coupled openness partially mediates the effect of inbound openness on sensing capacity. Also, coupled openness positively affects sensing capacity. Openness and dynamic capabilities views are complementary; small business managers embracing inbound and coupled openness enhance their sensing capacity.